The product selectivity zones in gas diffusion electrodes during the electrocatalytic reduction of CO2. Issue 11 (13th October 2021) - Möller, Tim; Ngo Thanh, Trung; Wang, Xingli; Ju, Wen; Jovanov, Zarko; Strasser, Peter
Abstract : The current work presents zones of distinct catalytic selectivity during Cu-based CO2 RR at high currents in gas diffusion electrodes. Abstract : Here we report on the most prominent factors influencing the performance of a Cu-based CO2 electrolyzer operating at high currents. Using a flow-electrolyzer design where CO2 gas feed passes directly through the electrode interacting with the Cu catalyst layer, we observed that the selectivity of the electrochemical CO2 reduction in (bulk) pH neutral media can greatly be influenced by adjusting the structure of the electrode. In this, the variations in catalyst loading and ionomer content can profoundly affect the selectivity of CO2 RR. We explore the hypothesis that this originates from the overall mass transport variations within the porous catalytic layer of the gas diffusion electrode. As further evidence for this, apart from the CO2 electrolysis results, we propose a special method to benchmark the reactant mass transport in flow-cells using oxygen reduction reaction (ORR) limiting current measurements. Our analysis suggests that a restriction of mass transport is highly desirable due to its connection to a local alkalization and corresponding suppression of pH-dependent reaction products, given the absence of local CO2 concentration limitations. We further show how the electrode structure can be used to push the observed catalytic CO2 reduction selectivity either towards C1 or C2+ products, dependent on the ionomer content and catalyst loading in a cathodic current range of 50 to 700 mA cm −2 . Measurements at various KHCO3 electrolyte concentrations agree with the notion of the local pH dictating the overall selectivity and point towards the presence of pronounced concentration gradients within the system. Overall, our work suggests that the differences in electrocatalytic CO2 reduction selectivity at high currents (in a range of pH neutral buffering electrolytes) largely originate from the local concentration gradients defined by the initial catalyst ink formulation and architecture of the catalytic layer, both of which represent a powerful tool for optimization in the production of selected value-added products.